Another Look at the Macroeconomic Information Content of Aggregate Earnings: Evidence from the Labor Market - Hann, Rebecca N.; Li, Congcong; Ogneva, Maria (The Accounting Review, 2021)
ABSTRACT We examine the macroeconomic information content of aggregate earnings from the labor market's perspective. We use insights from the labor economics literature to characterize the information contained in aggregate GAAP earnings and its components that is relevant for predicting aggregate job creation and destruction. Our results suggest that not only does aggregate earnings news convey information about future labor market aggregates, but its information content is incremental to other macroeconomic variables at near-term horizons. Further, the source of this information stems primarily from two earnings components: aggregate core earnings and special items. Shocks to core earnings signal persistent changes in economy-wide profitability that predict aggregate job creation up to four quarters ahead, while shocks to special items predict job destruction up to one quarter. Taken together, our results suggest that aggregate earnings contain useful information about future labor market conditions, with the nature of such information varying across earnings components. JEL Classifications: E37; E44; G17; G24; M41.